7 good reasons not to grow up - Gownley, Jimmy (Graphix, 2020)
Middle schooler Kirby Finn has it all in Greycliff Academy--fame, charm, brains, and a seemingly unbreakable streak of luck as evidenced by his viral videos "Seven Good Reasons Not to Grow Up." He aims to show the world just how dumb adults can be, and why kids should not want to become one of them. However, there is a secret Kirby has been hiding, and when Raja, his best friend, finds out about it, both may have to grow up fast.